The development of Serbian aviation and aviation signal stations and their significance on the Salonica front - Stanković Vitomir A. (Војно дело, 2018)
The development of human society and human conscience has contributed to the general progress in different spheres. Man, observing the surroundings, has always tended to adjust the environment to his needs. Thus, at one point, looking into the sky, he experienced a desire to fly in the vast space above him and be free like a bird. Such ideas have not just been a dream, but represented a need to test the human capabilities, too. Hence he has started, initially in a primitive way, and later with more sophistication, to contrive mechanisms, which would take him into free and yet unexplored sky. The first balloon flight was performed out in the long gone year of 1783, when the Montgolfier brothers flew over Paris. George Cayley, an English engineer, carried out several flights between 1804 and 1853. He was the first to construct a flying machine with fixed wings and separate systems for take-off, motion and control. In 1874 Felix du Temple de la Croix, a navy officer, constructed a flying device resembling the wings of a bird, with a wheel retracting into the base, a propeller and a 6 HP motor. Clement Ader, a French engineer, constructed in 1890 a flying device called Eole powered by a steam engine with four cylinders, 20 HP and four propellers. Otto Lilienthal, a German civil engineer, managed to perform the first safe flight in history. His scientific approach was adopted by the Wright brothers. Orville and Wilbur Wright constructed the first 'successful' airplane in the world, whose flight on 17 December 1903 was fully controlled. Later on, they developed a fixed airplane wing and introduced electronic adjustments in the airplane.